2008
DOI: 10.1080/15376510701728455
|View full text |Cite
|
Sign up to set email alerts
|

Increased Antioxidant Potential and Decreased Free Radical Production in Response to Mild Injection of Crude Venom,Cerastes cerastes gasperetti

Abstract: The purpose of this study was to examine the effects of Cerastes cerastes gasperetti crude venom (CCV) on free radical (FR) production and biological antioxidant potential (BAP). Thirty male rats, matched with age and weight, were divided randomly into three groups: control (C), negative control (NC), and experimental (E). Animals in the control group served as control for needlestick and venom injection. Animals in the negative control group, which served as control for venom-induced effects, were injected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The risk of injury from radiation can diminish the value of radiotherapy and contribute to complications for long-term cancer survivors [ 3 ]. Ionizing radiation interrupts cell functions through radiolysis of water and the production of reactive oxygen species (ROS) or reactive nitrogen species (RNS) [ 4 , 5 ]. Excessive production of ROS and RNS promotes oxidative stress, which can affect all cellular components, including single or double DNA strand breaks [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of injury from radiation can diminish the value of radiotherapy and contribute to complications for long-term cancer survivors [ 3 ]. Ionizing radiation interrupts cell functions through radiolysis of water and the production of reactive oxygen species (ROS) or reactive nitrogen species (RNS) [ 4 , 5 ]. Excessive production of ROS and RNS promotes oxidative stress, which can affect all cellular components, including single or double DNA strand breaks [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that Cr enters the cells either binds to ligands or participates in redox processes that induce oxidative stress. Due to high-dose and long-term treatment of Cr 3+ the antioxidative capacity decreased leads to the oxidative stress [19]. In redox reactions, Cr 3+ may induce lipid oxidation or deplete glutathione.…”
Section: Discussionmentioning
confidence: 99%